Laju Fotosintesis pada Tanaman Kelapa Sawit Terinfeksi Karat daun Cephaleuros virescen - Agus Susanto; Agus Eko Prasetyo; Hari Priwiratama; Muhdan Syarovi (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2020)
Photosynthesis Rate of Oil Palm Infected by Red Rust Cephaleuros virescens The incidence of oil palm red rust disease caused by Cephaleuros virescens tends to increase in Indonesia. However, the loses due to this disease has never been measured quantitatively. This study was conducted to measure the rate of photosynthesis on 5-year-old palms with 3 infection categories, i.e. mild, medium, and heavy infection. Field observation of oil palm in Kalianta showed that the infection of red rust disease occurred starting from lower to the upper fronds. Higher infection was prevalently on the adaxial than abaxial leaf. The red rust infection on frond number 17 or younger severely affects the photoshynthesis rate of the oil palm. On the palm with heavy infection category, the photosynthesis rate on frond number 9 was decreased up to 42.48%, i.e. from 15.51 µmol to 8.92 µmol, compared to that with mild infection.